Stainless steel part and kovar alloy part sealing method, sealing material and precursor material
By using microcrystalline glass with the main crystal phase of garnet crystal as the sealing material, the crushing and air leakage problems of conventional glass when encapsulating stainless steel and coval alloy 4J50 are solved, and the sealing effect with high strength and suitable thermal expansion coefficient is achieved.
Patent Information
- Application Number
- CN202510010381.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-03
AI Technical Summary
Conventional glass is not suitable for packaging stainless steel and coval alloy 4J50, and it is prone to glass breakage, air leakage and other problems.
Microcrystalline glass with the main crystal phase of garnet crystal is used as the sealing material, and a glass prefixed piece with a thermal expansion coefficient of 11.5×10-6℃-1 to 13.0×10-6℃-1 was prepared and packaged at 750℃-850℃.
The strength and thermal expansion coefficient of the sealing material are improved, the glass breakage and air leakage are avoided, and the sealing needs of stainless steel and coval alloys are met.
Smart Images

Figure CN119797764A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of electronic packaging, and in particular to a sealing method, sealing material and precursor material for stainless steel parts and Kovar alloy parts. Background Art
[0002] Metal penetrations are widely used in the field of electronics. They are usually assembled from a metal shell, a metal needle body, and a sealing material. The metal shell is usually made of kovar, stainless steel, pure titanium, copper, and other materials, while the metal needle body is usually kovar. Traditional sealing materials are usually metal solders. In order to prevent the metal solder from causing a short circuit between the metal shell and the metal needle body, it is usually necessary to ceramicize the metal shell and the needle body, that is, sinter a layer of ceramic on the sealing surface of the metal shell and the needle body to ensure insulation. However, the temperature of this ceramicization treatment is often very high, and the process is cumbersome, resulting in a very low yield rate. Glass-based sealing materials use the characteristics of glass that can deform at high temperatures and can wet the metal surface to directly seal the metal shell and the metal needle body. And because glass-based materials themselves are insulating, there is no need to worry about short circuits.
[0003] Stainless steel is widely used in metal shells as a metal with excellent performance and low price. Kovar 4J50 is more suitable for penetrating parts with stainless steel, a metal with high thermal expansion coefficient, due to its high thermal expansion coefficient. However, the packaging structure composed of conventional glass, stainless steel shell and Kovar 4J50 is prone to glass breakage and air leakage. Summary of the invention
[0004] The main purpose of the present invention is to provide a sealing method, sealing material and precursor material for stainless steel parts and Kovar alloy parts, so as to solve the technical problem that conventional glass is not suitable for packaging stainless steel and Kovar alloy 4J50.
[0005] To achieve the above object, the present invention provides a sealing precursor material for sealing stainless steel and Kovar alloy, wherein the glass prepared from the sealing precursor material comprises, by mass fraction:
[0006]
[0007] According to an embodiment of the present application, the glass prepared from the sealing precursor material comprises, by mass fraction:
[0008]
[0009] The present application also provides a sealing material for sealing stainless steel and Kovar alloy, which is prepared using the glass powder prepared from the above-mentioned sealing precursor material as a raw material; the sealing material is a microcrystalline glass whose main crystal phase is leucite crystal, and whose thermal expansion coefficient at room temperature to 500°C is 11.5×10-6 ℃ -1 ~13.0×10 -6 ℃ -1 .
[0010] The present application also provides a method for sealing a stainless steel part and a Kovar alloy part, comprising the following steps:
[0011] The sealing precursor material is prepared into a base glass;
[0012] The base glass is crushed into powder, and granulated to obtain granulated powder;
[0013] After forming the granulated powder into a green body of a target shape, the green body is fired to obtain a glass pre-sintered part;
[0014] After assembling the glass pre-sintered part with the stainless steel part and the Kovar alloy part, the temperature is raised to 750° C. to 850° C., and kept at this temperature for 30 min to 120 min, and then cooled to room temperature.
[0015] According to the implementation mode of the present application, after the glass pre-sintered part is assembled with the stainless steel part and the Kovar alloy part, the temperature is raised to 750° C. to 850° C. at a rate not higher than 3° C. / min.
[0016] According to the implementation mode of the present application, after keeping warm for 30 to 120 minutes, the temperature is lowered to room temperature at a rate not higher than 3°C / min.
[0017] According to an embodiment of the present application, the step of firing the target shape blank comprises:
[0018] The target shape blank is heated from room temperature to 650° C. to 750° C. at a rate not higher than 3° C. / min, and kept at this temperature for 10 min to 120 min.
[0019] According to an embodiment of the present application, the step of preparing the sealing precursor material into a base glass comprises:
[0020] SiO 2 、Al 2 O 3 , K 2 CO 3 、Na 2 CO 3 、ZnO、SrCO 3 , B 2 O 3 , Li 2 CO 3 、CaCO 3 and MgO according to mass fraction, and the mixture is ball-milled;
[0021] The product obtained after ball milling is melted and then water quenched to obtain the basic glass.
[0022] According to an embodiment of the present application, the step of crushing the base glass into powder comprises:
[0023] After the base glass is dried, it is ball-milled into powder of 300-500 meshes.
[0024] According to an embodiment of the present application, the temperature in the melting step is 1500-1600°C.
[0025] In the above-mentioned sealing precursor material for sealing stainless steel parts and Kovar alloy parts, the raw material selection and content selection are reasonable, and the sealing material is prepared by using the glass powder prepared from the sealing precursor material as the raw material. The sealing material is in the form of a glass phase with leucite crystals inside, so that its thermal expansion coefficient can reach 11.5×10 -6 ℃ -1 ~13.0×10 -6 ℃ -1 (Room temperature ~ 500℃) meets the requirements of sealing stainless steel parts and Kovar alloy parts, and the sealing material is also high in strength and not easy to break. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0027] Figure 1 1 is the XRD diagram of the glass pre-sintered part of Example 1 and the sealing material after packaging.
[0028] Figure 2 It is the thermal expansion behavior per unit length of Example 1 and Example 2 after crystallization.
[0029] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with the implementation methods and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] It should be noted that all directional indications (such as up, down, etc.) in the embodiments of the present invention are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.
[0032] In addition, in the present invention, the descriptions such as "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" or "second" may explicitly or implicitly include at least one of the features.
[0033] Furthermore, the technical solutions between the various embodiments of the present invention may be combined with each other, but this must be based on the fact that they can be implemented by ordinary technicians in the field. When the combination of technical solutions is mutually contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0034] The present invention provides a sealing precursor material for sealing stainless steel and Kovar alloy. The glass prepared from the sealing precursor material comprises, by mass fraction:
[0035]
[0036]
[0037] The above components SiO 2 、Al 2 O 3 , K 2 O、Na 2 O, ZnO, SrO, B 2 O 3 , Li 2 The sum of the weight percentages of O, CaO and MgO is 100%.
[0038] The raw materials of the sealing precursor material have various compositions. Regardless of the composition, as long as it meets the above conditions (mass fraction requirements) in the glass prepared after melting (ie, the subsequent base glass), it will be fine.
[0039] For example, some of the raw materials of the sealing precursor material may be the same as the corresponding oxides in the base glass. 2 、Al 2 O 3 , ZnO, B 2 O 3 , MgO and other raw materials with relatively stable properties at room temperature.
[0040] Other oxides in the base glass are unstable at room temperature, such as K 2 O、Na 2 O, SrO, Li 2 O, CaO, so the raw materials of the sealing precursor material are materials that can form the above oxides in a molten state. For example, the carbonate form (K 2 CO 3 、Na 2 CO 3 、SrCO 3 , Li 2 CO 3 、CaCO 3 ) and / or the corresponding nitrate form of the above oxides (KNO 3 、NaNO 3 、Sr(NO 3 ) 2 、LiNO 3 、Ca(NO 3 ) 2 ).
[0041] It can be understood that the raw materials of the sealing precursor material are 2 、Al 2 O 3 , ZnO, B 2 O 3 For the part corresponding to MgO, in addition to directly using the corresponding oxide, the carbonate form corresponding to the above oxide and / or the nitrate form corresponding to the above oxide can also be used.
[0042] The sealing precursor material used to seal stainless steel parts and Kovar alloy parts is the initial raw material for making the sealing material. The sealing precursor material is SiO 2 、Al 2 O 3 , K 2 O、Na 2 O, ZnO, SrO, B 2 O 3 , Li 2 O, CaO and MgO. Among them, SiO 2 、Al 2 O 3 and K 2 O is added to precipitate leucite crystals (KAlSi 2 O 6 ), according to SiO 2 -Al 2 O 3 -K 2 O ternary phase diagram shows that the weight percentage of the leucite phase region is: SiO2 46~74%, K 2 O 12~41%, Al 2 O 3 7~32%, based on which the SiO in the present invention is optimized 2 、Al 2 O 3 and K 2 The weight percentage of O. 2 O, ZnO, SrO, B 2 O 3 , Li 2 O, CaO, and MgO are added to lower the sealing temperature of the base glass, because these oxides are glass fluxes.
[0043] Exemplarily, the above raw materials are in a mixed state, and the sealing precursor material is in a mixed powder state. The corresponding powders of the above multiple raw materials are mixed uniformly. When preparing the basic glass, it is directly melted.
[0044] Exemplarily, the above raw materials are in an independently packaged state, and the sealing precursor material is a collection of independently packaged raw materials. When preparing the base glass, the raw materials are unpacked, mixed evenly, and then melted.
[0045] The sealing precursor material is prepared into a basic glass, such as by melting and then quenching the basic glass, and then the basic glass is crushed to be used as a raw material for the sealing material.
[0046] The study found that the thermal expansion coefficient of Kovar alloy 4J50 is 10.2×10 -6 ℃ -1 (Room temperature ~ 500℃), the thermal expansion coefficient of stainless steel is 17.5×10 -6 ℃ -1 (Room temperature ~ 500℃). According to the thermal stress model analysis, the appropriate thermal expansion coefficient of glass-based sealing materials used to encapsulate stainless steel and Kovar alloy 4J50 is 11.5×10 -6 ℃ -1 ~13.0×10 -6 ℃ -1 (Room temperature to 500°C), the thermal expansion coefficient is relatively high and exceeds the normal thermal expansion coefficient range of glass.
[0047] For the through-type sealing structure, the glass sealing material will be subjected to thermal stress in the axial, circumferential and radial directions. Since glass materials are compressive but not tensile, the compressive stress should be allowed to withstand as much as possible in the glass body, but it should not be too large, and it is best not to exceed 400MPa. The thermal stress model analysis shows that for the Kovar alloy-stainless steel through-piece mentioned above, when the thermal expansion coefficient of the glass sealing material is greater than 13.0×10-6 ℃ -1 (room temperature ~ 500℃), tensile stress will be generated in the circumferential direction, making it easy to break. When the thermal expansion coefficient of the glass sealing material is less than 11.5×10 -6 ℃ -1 (Room temperature ~ 500℃), excessive axial compressive stress can also cause cracking in the glass.
[0048] In the above-mentioned sealing precursor material for sealing stainless steel parts and Kovar alloy parts, the raw material selection and content selection are reasonable, and the sealing material is prepared by using the glass powder prepared from the sealing precursor material as the raw material. The sealing material is in the form of a glass phase with leucite crystals inside, so that its thermal expansion coefficient can reach 11.5×10 -6 ℃ -1 ~13.0×10 -6 ℃ -1 (Room temperature ~ 500℃) meets the requirements of sealing stainless steel parts and Kovar alloy parts, and the strength of the sealing material is also relatively high.
[0049] According to an embodiment of the present application, the glass prepared from the sealing precursor material comprises, by mass fraction:
[0050]
[0051]
[0052] The present application also provides a sealing material for sealing stainless steel and Kovar alloy, which is prepared using the glass powder prepared from the above-mentioned sealing precursor material as a raw material; the sealing material is a microcrystalline glass whose main crystal phase is leucite crystal, and whose thermal expansion coefficient at room temperature to 500°C is 11.5×10 -6 ℃ -1 ~13.0×10 -6 ℃ -1 .
[0053] The sealing material is formed by firing glass powder prepared from a sealing precursor material, sintering at 750° C. to 850° C., and then cooling to complete packaging.
[0054] The sealing material of the present application can be packaged at 750℃~850℃, which is much lower than the sealing temperature of 950℃ or more in the traditional metal ceramic process. The packaging process of first packaging in the form of glass phase and then precipitating the white garnet crystal phase not only ensures the packaging quality but also makes the thermal expansion coefficient of the sealing material meet the requirements and improves the strength of the sealing material. Finally, the thermal expansion coefficient of the sealing material is controlled at 11.5×10 -6 ℃ -1 ~13.0×10 -6 ℃ -1(Room temperature ~ 500℃), which can ensure that the sealing material is subjected to compressive stress of moderate size, which is beneficial to improving the yield rate of the penetration parts and the sealing life.
[0055] The present application also provides a method for sealing a stainless steel part and a Kovar alloy part, comprising the following steps:
[0056] S100: preparing the above-mentioned sealing precursor material into a base glass.
[0057] As mentioned above, the sealing precursor material is a raw material for preparing basic glass, which is a collection of various oxides. The basic glass is prepared in the same way as glass, and the specific method is not limited. For example, the components of the sealing precursor material are mixed evenly and melted to prepare the basic glass.
[0058] In some embodiments, the step of preparing the sealing precursor material into a base glass comprises:
[0059] S110: SiO 2 、Al 2 O 3 , K 2 CO 3 、Na 2 CO 3 、ZnO、SrCO 3 , B 2 O 3 , Li 2 CO 3 、CaCO 3 and MgO according to mass fraction, and the mixture is ball milled.
[0060] SiO 2 、Al 2 O 3 , K 2 CO 3 、Na 2 CO 3 、ZnO、SrCO 3 , B 2 O 3 , Li 2 CO 3 、CaCO 3 and MgO are weighed according to the composition of each substance in the sealing precursor material, and mixed to obtain the sealing precursor material.
[0061] For example, analytically pure SiO 2 、Al 2 O 3 , K 2 CO 3 、Na 2 CO 3、ZnO、SrCO 3 , B 2 O 3 , Li 2 CO 3 、CaCO 3 and MgO, grind the raw materials thoroughly with a planetary ball mill, and then take them out and dry them.
[0062] S120: Melting the product obtained after ball milling, and then quenching with water to obtain the basic glass.
[0063] After the sealing precursor material is melted, molten glass is obtained. The molten glass is quenched by water to cool it suddenly, solidify it and break it into fine particles, so that the glass structure of the molten material is fixed. For example, the molten glass is directly put into water and sprayed with high-pressure water to quench the glass into glass particles, that is, the base glass.
[0064] Exemplarily, the powder obtained by ball milling and drying is placed in a corundum crucible, placed in a box-type resistance furnace, heated to 1550°C in an air atmosphere, melted at the constant temperature for 2 hours, and then the melt is poured into water at 1400°C for quenching to obtain a basic glass block.
[0065] S200: crushing the base glass into powder, and granulating it to obtain granulated powder.
[0066] For example, the base glass is ball-milled into a powder of 300-500 meshes, and then the base glass powder is granulated to obtain granulated powder to facilitate subsequent pressing and molding. In some embodiments, the base glass is dried and then pulverized.
[0067] S300: After the granulated powder is formed into a target shape blank, it is fired to obtain a glass pre-sintered part. The target shape blank corresponds to the sealing structure formed by the sealing material in the sealing state, and its shape and size are basically consistent with the sealing structure. The glass pre-sintered part is mainly a pure glass phase, and no leucite crystal phase is precipitated. Because the pure glass phase is easier to infiltrate the metal surface, it helps to improve the sealing quality.
[0068] There are many ways of forming, for example, placing the granulated powder in a corresponding mold and pressing it into shape, and then firing it, during which degreasing, pre-firing and vitrification are completed to obtain a glass pre-fired part.
[0069] S400: After assembling the glass pre-sintered part with the stainless steel part and the Kovar alloy part, the temperature is raised to 750° C. to 850° C., and kept at this temperature for 30 min to 120 min, and then cooled to room temperature.
[0070] The glass pre-burned part is assembled between the stainless steel part and the Kovar alloy part. The glass pre-burned part, the stainless steel part and the Kovar alloy part are usually assembled at room temperature. Taking the target product as a through-piece as an example, the stainless steel part is a stainless steel shell, and the Kovar alloy part is a Kovar alloy needle body. The glass pre-burned part, the stainless steel shell and the Kovar alloy needle body are assembled into a through-piece, and the through-piece is heated as a whole, kept at 750℃~850℃ for 30min~120min, and then cooled to room temperature.
[0071] During the heat preservation process, the leucite crystal phase will gradually precipitate from the glass matrix phase, thereby achieving the purpose of increasing the thermal expansion coefficient of the sealing material and improving the strength of the sealing material. After completing the above steps, the glass pre-sintered part is transformed into a sealing part, and the material of the sealing part is the sealing material. Exemplarily, the entire penetration part is heated in a box-type resistance furnace.
[0072] In the above-mentioned sealing method of stainless steel parts and Kovar alloy parts, the sealing material can be packaged at 750℃~850℃, which is much lower than the traditional sealing temperature of more than 950℃. The packaging process of first packaging in the form of glass phase and then precipitating the white garnet crystal phase not only ensures the packaging quality but also makes the thermal expansion coefficient of the sealing material meet the requirements and improves the strength of the sealing material. Finally, the thermal expansion coefficient of the sealing material is controlled at 11.5×10 -6 ℃ -1 ~13.0×10 -6 ℃ -1 (Room temperature ~ 500℃), which can ensure that the sealing material is subjected to compressive stress of moderate size, which is beneficial to improving the yield rate of the penetration parts and the sealing life.
[0073] In some embodiments, after the glass pre-sintered part is assembled with the stainless steel part and the Kovar alloy part, the temperature is raised to 750° C. to 850° C. at a rate not higher than 3° C. / min. This lower heating rate helps to evenly transfer heat to different parts of the material, reducing material deformation and thermal stress.
[0074] In some embodiments, after keeping warm for 30 to 120 minutes, the temperature is lowered to room temperature at a rate no higher than 3° C. / min.
[0075] In some embodiments, the step of firing the target shape green body comprises:
[0076] The target shape blank is heated from room temperature to 650°C to 750°C at a rate not higher than 3°C / min, and kept at this temperature for 10min to 120min. During the heating process, since the heating rate is not high, degreasing can be completed during the heating process, and then the pre-sintering, i.e., vitrification, of the glass can be completed during the keeping process at 650°C to 750°C.
[0077] In some embodiments, the temperature in the melting step is 1500-1600°C.
[0078] The technical solution of the present application is described below in conjunction with specific embodiments.
[0079] Example 1
[0080] This embodiment provides a sealing precursor material for sealing stainless steel and Kovar alloy.
[0081] A sealing precursor material is provided, wherein the glass prepared from the sealing precursor material comprises, by mass fraction:
[0082]
[0083] The preparation process is as follows: weigh analytically pure SiO 2 、Al 2 O 3 , K 2 CO 3 、Na 2 CO 3 、ZnO、SrCO 3 , B 2 O 3 , Li 2 CO 3 、CaCO 3 and MgO, the raw materials are fully mixed and ground with a planetary ball mill, and then taken out and dried to obtain a sealing precursor material.
[0084] This embodiment also provides a method for sealing a stainless steel part and a Kovar alloy part, comprising the following steps:
[0085] S10: The sealing precursor material of Example 1 is placed in a corundum crucible, placed in a box-type resistance furnace, heated to 1550° C. in an air atmosphere, melted at the constant temperature for 2 hours, and then the melt is poured into water at 1400° C. for quenching to obtain a basic glass block.
[0086] S20: drying the basic glass block and grinding it into a powder of 300-500 meshes by ball milling, and then granulating the basic glass powder to obtain granulated powder to facilitate subsequent pressing and molding.
[0087] S30: After the granulated powder is dry-pressed and formed, it is placed in a box-type resistance furnace, and the temperature is raised from room temperature to 740°C at a rate of 2°C / min and kept at 740°C for 30 minutes to complete degreasing, pre-sintering and vitrification, thereby obtaining a glass pre-sintered part.
[0088] S40: The glass pre-sintered part, the stainless steel shell and the Kovar alloy needle body are then assembled into a through-piece, which is then placed in a box-type resistance furnace and heated from room temperature to 830°C at a rate of 2°C / min and kept at 830°C for 60 minutes to complete the packaging, and then cooled to room temperature at a rate of 2°C / min. During the heat preservation and packaging process, the base glass also precipitates a white garnet crystal phase.
[0089] Example 2
[0090] This embodiment provides a sealing precursor material for sealing stainless steel and Kovar alloy.
[0091] A sealing precursor material is provided, wherein the glass prepared from the sealing precursor material comprises, by mass fraction:
[0092]
[0093] The glass prepared by the sealing precursor material does not include B 2 O 3 The preparation process is as follows: weigh analytically pure SiO 2 、Al 2 O 3 , K 2 CO 3 、Na 2 CO 3 、ZnO、SrCO 3 , Li 2 CO 3 、CaCO 3 and MgO, the raw materials are fully mixed and ground with a planetary ball mill, and then taken out and dried to obtain a sealing precursor material.
[0094] This embodiment also provides a method for sealing a stainless steel part and a Kovar alloy part, comprising the following steps:
[0095] The difference from Example 1 is that:
[0096] In step S30:
[0097] The granulated powder was dry-pressed and placed in a box-type resistance furnace. The temperature was raised from room temperature to 700°C at a rate of 2°C / min and kept at 700°C for 40 minutes to complete degreasing, pre-sintering and vitrification to obtain a glass pre-sintered part.
[0098] In step S40:
[0099] The glass pre-sintered part, stainless steel shell and Kovar alloy needle were assembled into a penetration part, and then placed in a box-type resistance furnace and heated from room temperature to 810℃ at a rate of 2℃ / min and kept at 810℃ for 40min to complete the packaging, and then cooled to room temperature at a rate of 2℃ / min. During the heat preservation and packaging process, the base glass also precipitated the white garnet crystal phase.
[0100] Example 3
[0101] This embodiment provides a sealing precursor material for sealing stainless steel and Kovar alloy.
[0102] A sealing precursor material is provided, wherein the glass prepared from the sealing precursor material comprises, by mass fraction:
[0103]
[0104] The preparation process is the same as that of Example 1.
[0105] This embodiment also provides a method for sealing a stainless steel part and a Kovar alloy part, comprising the following steps:
[0106] The difference from Examples 1 and 2 is that:
[0107] In step S30:
[0108] The granulated powder was dry-pressed and placed in a box-type resistance furnace. The temperature was raised from room temperature to 680°C at a rate of 2°C / min and kept at 680°C for 110 min to complete degreasing, pre-sintering and vitrification to obtain a glass pre-sintered part.
[0109] In step S40:
[0110] The glass pre-sintered part, stainless steel shell and Kovar alloy needle were assembled into a through-piece, and then placed in a box-type resistance furnace. The temperature was raised from room temperature to 790℃ at a rate of 2℃ / min and kept at 790℃ for 100min to complete the packaging. Then, the temperature was lowered to room temperature at a rate of 2℃ / min. During the heat preservation and packaging process, the base glass also precipitated a white garnet crystal phase. The thermal expansion coefficient of the sealing material is 12.3×10 -6 ℃ -1 (Room temperature ~ 500℃).
[0111] Example 4
[0112] This embodiment provides a sealing precursor material for sealing stainless steel and Kovar alloy.
[0113] A sealing precursor material is provided, wherein the glass prepared from the sealing precursor material comprises, by mass fraction:
[0114]
[0115] The glass prepared from the sealing precursor material does not include Li 2 O. The preparation process is as follows: weigh analytically pure SiO 2 、Al 2 O 3 , K 2 CO 3、Na 2 CO 3 、ZnO、SrCO 3 , B 2 O 3 、CaCO 3 and MgO, the raw materials are fully mixed and ground with a planetary ball mill, and then taken out and dried to obtain a sealing precursor material.
[0116] This embodiment also provides a method for sealing a stainless steel part and a Kovar alloy part, comprising the following steps:
[0117] The difference from Examples 1, 2 and 3 is that:
[0118] In step S30:
[0119] The granulated powder was dry-pressed and placed in a box-type resistance furnace. The temperature was raised from room temperature to 720°C at a rate of 2°C / min and kept at 720°C for 60 min to complete degreasing, pre-sintering and vitrification, thereby obtaining a glass pre-sintered part.
[0120] In step S40:
[0121] The glass pre-sintered part, stainless steel shell and Kovar alloy needle were assembled into a penetration part, and then placed in a box-type resistance furnace and heated from room temperature to 820℃ at a rate of 2℃ / min and kept at 820℃ for 60min to complete the packaging. Then, it was cooled to room temperature at a rate of 2℃ / min. During the heat preservation and packaging process, the base glass also precipitated a white garnet crystal phase. The thermal expansion coefficient of the sealing material is 12.5×10 -6 ℃ -1 (Room temperature ~ 500℃).
[0122] Comparative Example 1
[0123] This comparative example provides a sealing precursor material for sealing stainless steel and Kovar alloy.
[0124] A sealing precursor material is provided, wherein the glass prepared from the sealing precursor material comprises, by mass fraction:
[0125]
[0126]
[0127] The preparation process is the same as that of Example 1.
[0128] The comparative example is used for sealing a stainless steel part and a Kovar alloy part, comprising the following steps:
[0129] The difference from Example 1 is that:
[0130] In step S30:
[0131] The granulated powder was dry-pressed and placed in a box-type resistance furnace. The temperature was raised from room temperature to 650°C at a rate of 2°C / min and kept at 650°C for 90 min to complete degreasing, pre-sintering and vitrification to obtain a glass pre-sintered part.
[0132] In step S40:
[0133] The glass pre-sintered part, stainless steel shell and Kovar alloy needle were assembled into a through-hole, and then placed in a box-type resistance furnace and heated from room temperature to 760℃ at a rate of 2℃ / min and kept at 760℃ for 60min to complete the packaging, and then cooled to room temperature at a rate of 2℃ / min. During the heat preservation and packaging process, the base glass also precipitated a white garnet crystal phase. 2 The content of O exceeds the protection range, resulting in a thermal expansion coefficient of 16.5×10 -6 ℃ -1 (Room temperature ~ 500℃).
[0134] Comparative Example 2
[0135] This comparative example adopts the sealing precursor material composition of Example 1, and the preparation process is also consistent with Example 1. S10, S20 and S30 of the sealing method are consistent with Example 1. However, S40 is different from Example 1: the glass pre-sintered part, the stainless steel shell, and the Kovar alloy needle body are then assembled into a through-piece, which is placed in a box-type resistance furnace and heated from room temperature to 950°C at a rate of 2°C / min and kept at 950°C for 60 minutes to complete the packaging, and then cooled to room temperature at a rate of 2°C / min. Since 950°C is beyond the protection scope of the patent of this invention, the base glass does not precipitate the white garnet crystal phase during the heat preservation and packaging process, so the thermal expansion coefficient of the sealing material is only 9.4×10 -6 ℃ -1 (Room temperature ~ 500℃).
[0136] Test Case
[0137] The glass pre-sintered part (i.e. before packaging) and the packaging structure after packaging of Example 1 were subjected to XRD test. The test results are shown in FIG. Figure 1 shown. Figure 1 3 is the XRD diagram of Example 1 before and after packaging. It can be seen from the figure that the sealing material is an amorphous pure glass phase before sealing, while a leucite crystal phase is precipitated after packaging.
[0138] The thermal expansion coefficients of the packaging materials of Example 1 and Example 2 were tested at different temperatures. The test results are as follows: Figure 2 The thermal expansion coefficient of the packaging material in Example 1 is 11.7×10 -6 ℃ -1(room temperature to 500°C), the thermal expansion coefficient of the packaging material of Example 2 is 12.9×10 -6 ℃ -1 (Room temperature ~ 500℃).
[0139] Similarly, the packaging materials of Example 3, Example 4, Comparative Example 1 and Comparative Example 2 were taken to test the thermal expansion coefficients at different temperatures.
[0140] Among them, referring to Table 1, the thermal expansion coefficient of the sealing material of Example 3 is 12.3×10 -6 ℃ -1 (Room temperature ~ 500℃).
[0141] The thermal expansion coefficient of the sealing material of Example 4 is 12.5×10 -6 ℃ -1 (Room temperature ~ 500℃).
[0142] The thermal expansion coefficient of the sealing material of Comparative Example 1 is 16.5×10 -6 ℃ -1 (Room temperature ~ 500℃).
[0143] The thermal expansion coefficient of the sealing material of Comparative Example 2 is 9.4×10 -6 ℃ -1 (Room temperature ~ 500℃).
[0144] The basic glass composition table (weight percentage) of each embodiment and comparative example is shown in Table 1.
[0145]
[0146]
[0147] It can be seen that in the embodiments of the present application, by selecting a suitable base glass and a sealing method, the thermal expansion coefficient can reach 11.5×10 -6 ℃ -1 ~13.0×10 -6 ℃ -1 The invention discloses a sealing material with a temperature of room temperature to 500°C, which can meet the requirements of sealing stainless steel parts and Kovar alloy parts, and the strength of the sealing material is also relatively high.
[0148] The above technical solutions of the present invention are only preferred embodiments of the present invention, and the patent scope of the present invention is not limited thereto. All equivalent structural changes made by using the contents of the present invention specification and drawings under the technical concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A sealing precursor material for sealing stainless steel and Kovar alloy, characterized in that: The glass prepared from the sealing precursor material comprises, by mass fraction:
2. The sealing precursor material for sealing stainless steel and Kovar alloy according to claim 1, characterized in that: The glass prepared from the sealing precursor material comprises, by mass fraction:
3. A sealing material for sealing stainless steel and Kovar alloy, characterized in that: The sealing material is prepared by using the glass powder prepared from the sealing precursor material according to claim 1 or 2 as a raw material; the sealing material is a microcrystalline glass whose main crystal phase is leucite crystal, and the thermal expansion coefficient at room temperature to 500°C is 11.5×10 -6 ℃ -1 ~13.0×10 -6 ℃ -1 .
4. A method for sealing a stainless steel part and a Kovar alloy part, characterized in that: The following steps are involved: The sealing precursor material according to claim 1 or 2 is prepared into a base glass; The base glass is crushed into powder, and granulated to obtain granulated powder; After forming the granulated powder into a green body of a target shape, the green body is fired to obtain a glass pre-sintered part; After assembling the glass pre-sintered part with the stainless steel part and the Kovar alloy part, the temperature is raised to 750° C. to 850° C., and kept at this temperature for 30 min to 120 min, and then cooled to room temperature.
5. The sealing method according to claim 4, characterized in that: After the glass pre-sintered part is assembled with the stainless steel part and the Kovar alloy part, the temperature is raised to 750° C. to 850° C. at a rate not higher than 3° C. / min.
6. The sealing method according to claim 4, characterized in that: After keeping warm for 30 to 120 minutes, cool to room temperature at a rate not higher than 3°C / min.
7. The sealing method according to claim 4, characterized in that: The step of firing the target shape green body comprises: The target shape blank is heated from room temperature to 650° C. to 750° C. at a rate not higher than 3° C. / min, and kept at this temperature for 10 min to 120 min.
8. The sealing method according to claim 4, characterized in that: The step of preparing the sealing precursor material into a base glass comprises: SiO2, Al2O3, K2CO3, Na2CO3, ZnO, SrCO3, B2O3, Li2CO3, CaCO3 and MgO are mixed according to mass fractions, and the mixture is ball-milled; The product obtained after ball milling is melted and then water quenched to obtain the basic glass.
9. The sealing method according to claim 8, characterized in that: The step of crushing the base glass into powder comprises: After the base glass is dried, it is ball-milled into powder of 300-500 meshes.
10. The sealing method according to claim 8, characterized in that: The temperature in the melting step is 1500-1600°C.
Citation Information
Patent Citations
Oxygen separation film component, binding method, and binding material
CN103396147A
Sealing material capable of resisting high temperature of 750 DEG C and preparation method of sealing material
CN106882921A
Soft lead-free low-temperature sealing glass and preparation method thereof
CN109455940A
Titanium and titanium alloy-sealing glass material as well as preparation method and application thereof
CN111018352A
Alkali borosilicate glass as well as preparation method and application thereof
CN117923794A